Audiovisual integration of the dynamic hand-held tool at different stimulus intensities in aging - Yang, Weiping; Yang, Xiangfu; Guo, Ao; Li, Shengnan; Li, Zimo; Lin, Jinfei; Ren, Yanna; Yang, Jiajia; Wu, Jinglong; Zhang, Zhilin (Frontiers in Human Neuroscience, 2022)
In comparison to the audiovisual integration of younger adults, the same process of older adults appears more complex and unstable. Previous research has found that stimulus intensity is one of the most important factors influencing the audiovisual integration. The present study used dynamic hand-held tool stimulus to compare the effect of stimulus intensity on audiovisual integration in aging. Behavioral results showed that both older and younger adults responded faster and higher hit rates to audiovisual stimulus than to visual and auditory stimulus. Further results of event-related potentials (ERPs) revealed that during the early stage of 60100 ms, in the low-intensity condition, audiovisual integration of anterior brain region was greater in older adults than in younger adults, however, in the high-intensity condition, audiovisual integration of the right hemisphere region was greater in younger adults than in older adults. Moreover, audiovisual integration was greater in the low-intensity condition than in the high-intensity condition in older adults during the 60100 ms, 120160 ms, and 220260 ms periods, showing inverse effectiveness. However, there was no difference in audiovisual integration of younger adults across different intensity conditions. The results suggested that there was an age-related dissociation between high- and low-intensity conditions with audiovisual integration of dynamic hand-held tool stimulus. Older adults showed greater audiovisual integration at lower intensity condition, which may be due to the activation of compensatory mechanisms.